Reinforced concrete beams strengthened in shear with NSM CFRP laminates : assessment of influencing parameters - Dias, Salvador J. E. (2013)
To appraise the performance of the Near surface mounted (NSM) technique with carbon fiber reinforced polymer (CFRP) laminates for the shear strengthening of reinforced concrete (RC) beams having a certain percentage of existing steel stirrups, an extensive experimental research was carried out. The influence on the effectiveness of the NSM shear strengthening technique of the following parameters was investigated: the concrete strength; the percentage of existing steel stirrups; the percentage and orientation of the CFRP laminates. To evaluate the influence, on the strengthening effectiveness, of already existing cracks when a beam is shear strengthened with NSM CFRP laminates, some of the RC beams were pre-cracked prior to their strengthening. A detailed description of the carried out experimental research and a discussion of the obtained results are done in the present paper.